Use of Occupational Performance Coaching for stroke survivors (OPC-Stroke) in late rehabilitation: A descriptive case study - Danika Belliveau; Isabelle Belliveau; Aniane Camiré-Raymond; Dorothy Kessler; Mary Egan (Scholarworks @ WMU, 2016)
Background: Stroke is a leading cause of disability in adults. Following stroke, 60% of people report needing help with everyday activities, and 80% report having very few meaningful activities. These restrictions often continue for years. This study explored the efficacy of Occupational Performance Coaching for stroke survivors (OPC-Stroke) on the participation level of adults in the later stage of stroke rehabilitation. Method: A descriptive case study design was used. One participant in the later stages of rehabilitation was recruited. Outcome measures for participation, goal performance and satisfaction, and emotional well-being were administered pre and postintervention to observe for direction of change. A semi-structured interview was carried out postintervention to explore the participant's experiences of the intervention. Results: The participant who took part in the study reported improvement with his goal performance and satisfaction. However, the level of participation did not improve and emotional well-being decreased. Qualitative data revealed an appreciation of the intervention and a recommendation of the intervention for others. Conclusion: OPC-Stroke was valued by the participant and shows promise for improving goal performance and satisfaction. Further research is necessary to determine the potential efficacy of OPC-Stroke in later stages of rehabilitation.